Teacher Identity in the Context of Current School Reforms in Kazakhstan - Khegay, Yuliya (NUGSE Research in Education, 2(2), 2017)
Kazakhstan is currently experiencing tremendous reforms in secondary education trying on best practices and experiences borrowed from abroad. Important figures at this stage are Nazarbayev Intellectual Schools (NIS) created to implement new approaches to teaching, learning and managing the school. The problem is that the major focus is given to the reforms themselves while the voices of those who actually enact them are usually ignored. This qualitative interview-based study aims at exploring the complex phenomenon of teacher identity in its relation to the present school reforms from NIS teachers’ perspective. The results of the study provide an insight on how teachers understand their professional identity within four dimensions: personal, social, professional and emotional, and how these are affected by different aspects of educational changes. The major findings have revealed that teaching-related aspect of school reforms has a mostly positive effect on teacher identity, whereas the administrative aspect tends to have a mostly negative influence.
Keywords: teacher identity; professionalism; school reforms; NIS